OUTCOMES OF CARPAL TUNNEL SYNDROME TREATMENT WITH TRANSVERSE CARPAL LIGAMENT RECONSTRUCTION - Bảo Lục, Nguyễn; Thành Toàn, Võ; Minh Dương, Nguyễn (Journal of Health and Aging, 2025)
Carpal tunnel syndrome (CTS) is a common neuropathy caused by median nerve compression, leading to pain, numbness, and weakened grip strength. The conventional treatment involves releasing the transverse carpal ligament (TCL), but this may reduce grip strength and biomechanical stability. TCL reconstruction may help maintain carpal tunnel integrity and protect the median nerve. This study aims to evaluate the clinical effectiveness of TCL reconstruction following CTS surgery. A prospective study was conducted on 13 patients diagnosed with CTS and undergoing TCL reconstruction at Thong Nhat Hospital from 12/ 2023 to 12/ 2024. After 12 months of follow-up, VAS scores significantly decreased from 6.4 ± 1.2 to 1.3 ± 0.8. Grip strength increased from 19.7 ± 5.6 kg to 29.4 ± 4.8 kg (p < 0.05). Two-point discrimination improved from 6.8 ± 1.5 mm to 4.3 ± 0.9 mm. The DASH score improved from 55.2 ± 6.7 to 18.4 ± 4.1. EMG findings showed improvement in 76,9% of patients. No cases of infection or recurrence were recorded. One patient (7.7%) had a transient palmar cutaneous branch injury, which resolved within six months. Patient satisfaction was reported at 92%. TCL reconstruction in CTS surgery significantly improves symptoms, preserves grip strength, and enhances hand function while minimizing complications. This method could be considered a standard option for CTS treatment.
Keywords: Carpal tunnel syndrome; transverse carpal ligament; median nerve; Grip strength; surgery; DASH score; EMG